Activity speckle images obtained from box fractal formalism. (October 2019) - Cap, N.L.; Rabal, H.; Grumel, E.; Buffarini, L.; Trivi, M.; Montecinos, M. Avendaño; Allendes, E. Baradit
Highlights: Recently we showed the possibility to apply the box fractal dimension to characterize static and dynamic speckle patterns in several situations. In this new manuscript, we extend the use of the box fractal algorithm to screen activity images. We show the application to segment activity images such as reading writing hidden by paper and papyrus and topography under drying paint. Segmentation of time series of incoherent images and dynamic speckle patterns can be resolved with a single versatile descriptor. Other BF algorithm possible applications may be found in other fields, such as ultrasound images, lateral synthetic aperture radar, etc. Abstract: We propose a generalized Box Fractal algorithm to segment activity speckle images. The time history of the intensity value at every pixel of the frames is taken as a time series. The plot of this time series is then considered an image in a plane, and its Box Fractal dimension is then calculated with the usual method. Its value is assigned to a pixel and an image is constructed that shows the activity from a fractal viewpoint. We show some cases of the application of this approach to segment images in different dynamic situations.